A parametric numerical analysis of femoral stem impaction. - Nicholas E Bishop; Phil Wright; Martin Preutenborbeck (PLoS ONE)
Press-fitted implants are implanted by impaction to ensure adequate seating, but without overloading the components, the surgeon, or the patient. To understand this interrelationship a uniaxial discretised model of the hammer/introducer/implant/bone/soft-tissues was developed. A parametric analysis of applied energy, component materials and geometry, and interactions between implant and bone and between bone and soft-tissues was performed, with implant seating and component stresses as outcome variables. To reduce the impaction effort (energy) required by the surgeon for implant seating and also reduce stresses in the hardware the following outcomes were observed: Reduce energy per hit with more hits / Increase hammer mass / Decrease introducer mass / Increase implant-bone resistance (eg stem roughness). Hardware stiffness and patient mechanics were found to be less important and soft tissue forces, due to inertial protection by the bone mass, were so low that their damage would be unlikely. This simple model provides a basic understanding of how stress waves travel through the impacted system, and an understanding of their relevance to implantation technique and component design.